Effect of online counselling on emotional outcomes during the COVID‐19 pandemic: An innovative group intervention for university students using the Brain Wave Modulation Technique. Issue 4 (28th December 2021) - Celia, Giovanna; Cavicchiolo, Elisa; Girelli, Laura; Limone, Pierpaolo; Cozzolino, Mauro
Abstract: Young people's mental health problems are a matter of concern during the COVID‐19 pandemic. Counselling services for university students by means of telemental support can help them to deal with psychological issues that they may be facing due to the pandemic. The present study investigated the effects of four once‐weekly online counselling sessions based on a mind‐body technique (the Brain Wave Modulation Technique; BWM‐T) on enhancing positive affect and on reducing negative affect and anxiety in a sample of 54 university students (96.3% females; M age = 21.31 years, SD = 2.09). An experimental design was conducted: the participants were randomly assigned to the intervention group, which received 15 min of a guided online BWM‐T session, or to the control group, which watched a 15‐min video on how to sustain their psychological well‐being. The results of a two‐factor mixed‐design analysis of variance (ANOVA) showed that the participants in the intervention group reported a significant increase in positive affect and a decrease in negative affect over time compared to those in the control group. They also reported a slight decrease in state anxiety compared to the control group, although this was just short of statistical significance. The information provided by this study, regarding emotional outcomes among university students after four brief online counselling sessions, suggests that such interventions could be an effective and sustainable way to reinforce young people's mental health during the COVID‐19 pandemic, as well as later in their university careers and adult lives.